GAMBARAN KEBIASAAN MEROKOK MASYARAKAT DI WILAYAH KERJA PUSKESMAS PEKUTATAN I KABUPATEN JEMBRANA PERIODE JUNI 2013 -JULI 2013 - Aditya Arya Adiputra (Intisari Sains Medis, 2015)
Smoking is can be harmful to our body health. Many disease was correlated to smoking habituation.Smoking can increase the risk of COPD. The negative effect of smoking is caused through a progressive decline in forced expiratory volume in 1 second (FEV1), which the results of reduction in lung function leading to shortness of breath. Smoking accounts for as many as 80% COPD-related deaths. Smokingresponsible for 80% of lung cancer that can increase the risk of developing lung cancer in developed countries five to ten fold. Indonesia with 65 million smokers on the third rank of nation has the largest smoker in the world. At the Puskesmas I Pekutatan, Jembrana Regency, the prevalence of smoker in that area has not been studied before.The research was conducted by using descriptive cross-sectional study on June 2013 until July 2013. Samples account of 50 people was selected by purposive and simple random sampling method with head of the family as a reasonable population at Puskesmas I Pekutatan, Jembrana Regency. From this research, 25 respondents (50%) has smoking habituation every day. Most of the smokers started to smoke between age 20 to 29 years (44%) and most of the respondent was smoke cigarettes with filters (88%). Many of the respondent are moderate smokers (60%) who smoke cigarettes between 10 to 20 every day. Considering the high prevalence of smoking, counseling and health promotion should be done about the risk of smoking for health.